'In silico' toxicology methods in drug safety assessment - Đukić-Ćosić Danijela; Baralić Katarina; Jorgovanović Dragica; Živančević Katarina; Javorac Dragana; Stojilković Nikola; Radović Biljana; Marić Đurđica; Ćurčić Marijana; Buha-Đorđević Aleksandra; Bulat Zorica; Antonijević-Miljaković Evica; et al. (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2021)
While experimental animal investigation has historically been the most conventional approach conducted to assess drug safety and is currently considered the main method for determining drug toxicity, these studies are constricted by cost, time, and ethical approvals. Over the last 20 years, there have been significant advances in computational sciences and computer data processing, while knowledge of alternative techniques and their application has developed into a valuable skill in toxicology. Thus, the application of in silico methods in drug safety assessment is constantly increasing. They are very complex and are grounded on accumulated knowledge from toxicology, bioinformatics, biochemistry, statistics, mathematics, as well as molecular biology. This review will summarize current state-of-the-art scientific data on the use of in silico methods in toxicity testing, taking into account their shortcomings, and highlighting the strategies that should deliver consistent results, while covering the applications of in silico methods in preclinical trials and drug impurities toxicity testing.